Keadilan Pajak Pertambahan Nilai di Indonesia: (Studi pada Perdagangan Barang dan Jasa Di Kota Samarinda) (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study, entitled "Value Added Tax Fairness in Samarinda City," analyzes the fairness of the 11% VAT rate under Law No. 7 of 2021 using socio-legal methods. The results show that although the single 11% VAT rate meets the principles of legality and horizontal justice because it applies equally to all consumers, this policy is not entirely fair from a vertical justice perspective. The regressive nature of the consumption tax tends to place a greater burden on low-income households. Field findings reveal that MSMEs feel burdened because the rate does not take into account their economic capacity, coupled with a lack of understanding of the input and output tax credit mechanisms. Administrative complexity and minimal education from tax authorities contribute to low compliance rates. This study recommends the implementation of a more flexible tiered VAT rate, strengthening tax education, providing technical assistance, and simplifying reporting for MSMEs to improve compliance and create more equitable tax justice.